REKONSTRUKSI EPISTEMOLOGI PENDIDIKAN ISLAM PADA MASA KOLONIAL BELANDA DAN IMPLIKASINYA TERHADAP DIKOTOMI PENDIDIKAN DI INDONESIA - Fathusy Syarif; Adam Maulana; Rafka Bulan Nafisa; Marhamah Putri; Aprizal Ahmad (CV. Adiba Aisha Amira, 2025)
This study aims to analyze the epistemology of Islamic education during the Dutch colonial period and its implications for the emergence of educational dichotomy in Indonesia. The research employs a qualitative approach with a library research method through the exploration of historical literature and conceptual analysis of relevant primary and secondary sources, including colonial educational archives, scholarly works, and the writings of Islamic reformers. The findings reveal that during the colonial era, Islamic education experienced epistemological marginalization due to the Dutch ethical policy emphasizing secular and rationalistic education. Meanwhile, Islamic institutions such as pesantren, surau, and madrasah maintained a knowledge paradigm rooted in revelation and classical scholarly traditions. The tension between these two systems generated an epistemological dualism that separated religious and secular sciences. The Western paradigm, which divorced spirituality from rationality, later influenced postcolonial educational policy, marginalizing moral and religious values within the modern education system. In the contemporary context, this dichotomy persists through the division between general and religious education, with an evaluation system prioritizing cognitive achievements over affective and spiritual dimensions. Therefore, reconstructing the epistemology of Islamic education is essential to harmonize revelation and reason, integrating both religious and modern sciences to create a holistic, civilized education system grounded in tawhid, morality, and humanity.